Schistosomiasis and associated iron-deficiency anaemia presenting decades after immigration from sub-Saharan Africa. Issue 4 (29th April 2019) - Leir, Sarah Anne; Foot, Oliver; Jeyaratnam, Dakshika; Whyte, Martin Brunel
Abstract : Chronic schistosomiasis and its intestinal manifestations can lead to anaemia. However, schistosomiasis resulting in anaemia is rare in the UK. This report aims to raise awareness of schistosomiasis in immigrants to the UK and prevent missed diagnosis.